Climate change impact on livelihood and vulnerability: a case study of mushar community in saptari district in Nepal - Sharma, Sushant (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2010.